Position paper on tuberculosis screening in patients with imune mediated inflammatory diseases who are candidates for biological therapy - Duarte,Raquel (2012)
Chronic immunosuppression is a known risk factor for tuberculosis. Our aim was to reach a consensus on screening and prevention of tuberculosis in patients with immune mediated inflammatory diseases who are candidates to biologic therapy. Methods: Critical appraisal of the literature and expert opinion on immunosuppressive therapies and risk of tuberculosis. Results and conclusion: The currently recommended method for screening is the tuberculin skin test and the interferon gamma assay, after exclusion of active tuberculosis. Positively screened patients should be treated for latent tuberculosis infection. Patients may start biological therapy after 1-2 months, as long as they are strictly adhering to and tolerating their preventive regimen.